A Failed Method? Reflections on Using Audio Diaries in Uganda With Young People Growing Up With HIV in the BREATHER Trial. (April 2019) - Bernays, Sarah; Paparini, Sara; Namukwaya, Stella; Seeley, Janet
In this article, we present a case study in which we consider our use of the audio diary method with young people (aged 10–24) living with HIV in Uganda in a longitudinal qualitative study conducted in a clinical randomized control trial. Despite initial enthusiasm for the method among participants to capture accounts of participants' experiences outside of the confines of the HIV clinic, the constraints the young people encountered in accessing sufficient privacy to confidently make recordings meant that no one elected to use them again in the study. Despite the insights the use of the method generated, the lack of acceptability led to its relative failure. This demonstrates that despite the call for innovation, there is an unwavering necessity when selecting methods that they align with the needs and preferences of our participants and with an attentive assessment of the local context in which illness narratives are produced.